An Analytic Economic Study of Agricultural Investment in Small Projects(Pattern: Apiculture) in Lattakia Governorate - Darwich, Nidal (Latakia University Journal -Biological Sciences Series, 2013)
Due to the economic and social importance of “Apiculture” as one of the most significant and major agricultural investment activities spread and practiced in Syria, and due to its importance represented in seeking to realize the main target of the agricultural policy represented in reaching the optimal investment of natural resources towards realizing food security; this research targeted the following objectives: Analyzing the production costs of the agricultural investment in small projects (Apiculture) in Lattakia Governorate Evaluatingeconomically honeybee breeding in Lattakia Governorate The most important results of this research are the following: The net farm revenue from one beehive amounted to SYP (4860.08/Hive/year). The net farm profit from one beehive amounted to SYP (4422.74/Hive/year). The total economic feasibility ofapiculture in Lattakia Governorate amounted to1.62. In comparison with the production costs, the profitability coefficient amounted to 76.64 %, and in comparison with the invested capital, it amounted to 41.06% which is a good indicator.